Analgesic Efficacy of Diclofenac and Ibuprofen/Paracetamol Combination in Post Extraction Cases - Giri, Anish; Palikhey, Anjan; Sah, Ajit Kumar; Upadhyay, Hari Prasad; Giri, Bijaya Laxmi (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Postoperative pain management is essential post-extraction for early mobilization and rehabilitation to enhance recovery and to reduce morbidity. Diclofenac and Ibuprofen and Paracetamol combination are two most common NSAIDs used in the postoperative pain control. Methods Two hundred fifteen patients (n=215) of age group 20-60 years who underwent extraction of upper or lower third molar impacted teeth were divided randomly into two groups (T1 and T2). T1 group (n=105) received Tab. Diclofenac 100mg and T2 group (n=110) received Tab Ibuprofen and Paracetamol combination. Analgesic efficacy of Diclofenac was compared with that of Ibuprofen and Paracetamol combination at post-op day 1, day 3 and day 5. Analgesic efficacy was measured using Visual Analogue Scale (VAS) and Verbal Rating Scale (VRS). Results Pain intensity decreased significantly at all the time points in both the groups. The analgesic efficacy of Diclofenac was significantly higher than Ibuprofen and paracetamol combination as estimated by VAS mean score at day 1 and day 3 post-operative period (p<0.001).But based upon the VRS mean score at post-opearative day 1, day 3 and day 5, there was no statistically significant difference between two treatment groups. Conclusions This study showed that Diclofenac potassium was more effective than Ibuprofen and Paracetamol combination for reducing postoperative pain associated with extraction of third molar impaction. Few number of patients in both treatment groups developed gastrointestinal upset.